2021
DOI: 10.48165/sajssh.2021.2501
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by B.P.L. Population in Availing Public Healthcare – Analysing Government Initiatives, Technology and Cultural Barriers in Aligarh District, U.P

Abstract: Public healthcare and government health initiative have always been in question regarding their availability, efficiency, and quality. This matter most for the poor section of society who have to go through various hurdles to avail the basic treatment, besides financial problems. The aim of this survey study was to analyze the present scenario of public healthcare system and the challenges in availing public healthcare faced by BPL (Below Poverty Line) and low-income population of Uttar Pradesh. A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Population residing in the Indian subcontinent has been facing various health and social challenges (Afzal et al, 2021), Bangladesh being no exception. The problem discussed in the present article translates into various other social problems as well as reproductive health problems Afzal and Das, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Population residing in the Indian subcontinent has been facing various health and social challenges (Afzal et al, 2021), Bangladesh being no exception. The problem discussed in the present article translates into various other social problems as well as reproductive health problems Afzal and Das, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 9 ] The situation gets further exacerbated for females of low-income households in rural areas with prevailing patriarchal norms. [ 10 ] The effect of CCC on human beings as well as the whole planet is multifaceted, ranging from disturbed ecosystems to rising sea levels. Research has shown the frequency of occurrence and magnitude of natural disasters (such as floods, landslides, and avalanches) have increased due to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…It is an idiosyncrasy of the male out-migration to leave their spouse back in their home country, usually with in-laws and kids (13) . While the migration does bring financial relief to families back home and add to the household income portfolio, but the added responsibilities of the WMM outweighs the benefits (14,15) . These women may be residing in rural areas or urban slums which further aggravates their health vulnerabilities (16) .…”
Section: Introductionmentioning
confidence: 99%